Risk Factor based on the Type of Stroke at RSUD Dr. Soetomo, Surabaya, Indonesia - Kurnia Dwi Artanti1, Santi Martini1, Sri Widati2, Muhammad Alminudin1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Stroke defined as a disease due to the trouble in the blood circulation which affected by several risk factors. It consists of fixed factors and unfixed factors. The fixed factor such as age, and gender, while unfixed factors including hypertension, blood glucose level, dyslipidemia, and job. Aims: This research aims to identify the distribution type of stroke, and risk factor which affecting the stroke patients in the RSUD Dr. Soetomo, Surabaya. Method: Research was designed as descriptive research to the stroke patient in the RSUD Dr. Soetomo, Surabaya. Various data was collected including age, gender, job, blood pressure, blood glucose level, and lipid profile when patient involved in the hospital at the first time, history of smoking, history of stroke in family. All of stroke patients in the RSUD Dr. Soetomo, Surabaya within October-December 2018 was addressed as subject in this research. Result: Result showed that ischemic stroke had the highest incidence rate in the hospital (72,6%), most of patient of stroke are male (56,2%) with age in less 65 years old (72,6%). Both hypertension 37(50,7%) respondent and smoking 29 (39,73%) respondent are the highest modified risk factor in this research. In the ischemic stroke, hypertension (62,3 %) is the highest modified risk factor. Whilst, in the hemorrhagic stroke, smoking (35 %) is the highest modified risk factor.. Moreover, the highest risk factor in all type of stroke is in age less than 65 years old (72,6%). Conclusion: Number of ischemic stroke case is higher than hemorrhagic stroke. Hypertension is defined as the highest risk factor in hemorrhagic stroke, while smoking is the highest risk factor of ischemic stroke